Certain Aspects of the Limits of Socratic Dialogue in Moral Education - Zelinová, Zuzana; Bizoň , Michal (Ruch Filozoficzny, 2023)
The main aim of our paper is to identify the potential limits of Socratic dialogue in moral education. These limits will be identified using a) the original ancient writings preserving several versions of Socrates’ dialogue, and b) modern writing on the Socrates’ dialogue in moral education. We will determine whether these limits are to be found in the writing of Plato or Xenophon, or rather in the problems and paradoxes of this type of education. We assume that a historical exploration of the original Socratic philosophy will help us to more easily identify the limits and problems in moral education. However, our intention is not to reject the Socratic dialogue as such, but merely to point out some of the potentially controversial aspects of its use in moral education.